Hydrocarbon generation kinetics and expulsion models of the Triassic Chang 9 lacustrine shales, Ordos Basin, China: Implications for the tight sandstone oil occurrence. (2nd August 2021) - Xu, Zhengjian; Wang, Yang; Jiang, Shu; Fang, Chao; Liu, Luofu; Wu, Kangjun; Shu, Yun; Feng, Yanjun; Li, Xin; Deng, Can
Abstract : Ordos Basin, a large lacustrine basin in the Triassic, possesses amounts of conventional and unconventional petroleum. In the basin, the Chang 7 shales have been studied extensively. Recent studies suggested that the crude oils accumulated in the Triassic Chang 9–8 should be mainly sourced by the Chang 9 shales [including the delta plain shale (DPS), delta front shale (DFS), and deep lake shale (DLS)]. The source rock (SR) potential, hydrocarbon generation (HG), and hydrocarbon expulsion (HE) characters of the Chang 9 shales should be analysed to make a comprehensive source rock evaluation. The shales are evaluated as excellent source rock potential, and the DLS is evaluated as the best potential. The HG–HE of the shales are analysed by utilizing two (closed and open systems) pyrolysis experiments. The DLS activation energy ( E a ) shows the narrowest distribution and has the lowest average value of 219.00 kJ/mol. The HG onsets and total amounts of the DFS, DPS, and DLS have been determined (165 Ma and 200 × 10 3  t/km 2, 157 Ma and 305 × 10 3  t/km 2, 154 Ma and 430 × 10 3  t/km 2 ), and the peak generation of the shales happened at 125–117 Ma, 127–100 Ma, and 125–100 Ma, respectively. The Chang 9 DFS, DPS, and DLS have reached the HE threshold at depths of 2, 250, 2, 500, and 2050 m, respectively, indicating large amounts of hydrocarbons have been expelled into the Lower Yanchang Formation (LYF). The tight sandstone oil reservoirs (TSORs) are mainly located in the areas where the organic‐rich shales are developed, especially in the northeastern study area. The areas between high‐value zones of source rock properties (e.g., thickness, Ro, total organic carbon, HG–HE intensity) are the sweet spots. Abstract : The tight sandstone oil reservoirs (TSORs) mainly located in the areas where the organic‐rich shales are developed, especially in the northeastern study area. The areas between high value zones of source rock properties (e.g., thickness, Ro, total organic carbon, HG‐HE intensity) are the sweet spots.